Challenges and Constraints Faced by Fisherwomen in Kashmir: A Comprehensive Examination (International Journal of Food and Nutritional Sciences, 2022)
The goal of this study is to shed light on the social, economic, personal, and health-related issues faced by the fisherwomen of the Kashmir Valley. Fisheries play a significant role in the food production process by providing the population's dietary protein demands and boosting the market. Even though they make up around half of Jammu & Kashmir's population, women are heavily involved in the fishing industry. They continue to be among the poorest in the state's most vulnerable categories, nonetheless. Fisherwomen are a vital component of post-harvest handling and marketing of fish products, serving as a vital link between producers and consumers. However, they face challenges due to increased competition, dwindling resources, and complex working conditions. Limited mobility further complicates their work, highlighting the need for capacity-building sessions and workshops to enhance their skills and generate additional income for their families. Encouraging women entrepreneurs in the fisheries sector is also essential. Addressing the various challenges to empower fisherwomen requires serious consideration by the State Government when formulating new development strategies